Polmon As A Strategy To Monitor And Control Political Discourse On Ai-Based Social Media - Quddus, Muh. Syah; Juniyanto, Akhmad Nur; Mutiara, Zulfa (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
Data released by We Are Social in 2024 shows that around 61.7% of the global population uses social media, with the average duration of use per day reaching 2 hours 31 minutes. In Indonesia alone, the rate of social media usage reaches 78% of the total population, making it one of the countries with the largest social media users in the world. This high usage rate is directly proportional to the high potential for the spread of divisive information, especially during political moments such as elections. This study aims to analyze the strategies that Indonesia can implement to overcome the challenges of political polarization on social media. The method used in this research is juridical-normative research, by analyzing secondary data from primary, secondary, and tertiary legal materials. The results show that POLMON is predicted to help identify disinformation, hate speech, and provocative content that triggers political polarization. This system has great potential to improve the quality of political discussions on social media, but its implementation must be done carefully so as not to violate privacy rights and freedom of expression.